ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN ASLI DAERAH (PAD) KABUPATEN/KOTA DI PROVINSI BALI - Suryadinata, Made Bagus; Mahaendra Yasa, I Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2025)
Regional financial independence is largely determined by the region's ability to realize its original regional income. Empirically, the problems experienced by the regions, aside from the realization that PAD has not yet reached the target, there are also quite large disparities in PAD achievement between regions. Factors that influence PAD include the number of tourist visits, investment and tourist expenditure. The research objectives are as follows. To analyze the influence of the number of tourist visits, investment and tourist expenditure simultaneously and partially on the PAD of districts/cities in Bali Province. This research uses a quantitative and associative approach. This research was conducted in districts/cities in Bali Province which include Jembrana, Tabanan, Badung, Gianyar, Klungkung, Bangli, Karangasem, Buleleng, and Denpasar City with the consideration that PAD experiences fluctuations and there is inequality between regions. The object of this research is the number of tourist visits, investment and tourist expenditure on district/city PAD in Bali Province. The method used in this research is panel data regression using the eviews application. The population in this study was all 9 districts/cities in Bali Province with 7 years of observation so the number of observations in this study was 63 observations. The research results show that the number of tourist visits, investment and tourist expenditure simultaneously have a significant effect on Regional Original Income. Partially, the number of tourist visits and tourist expenditure have a positive and significant effect on Regional Original Income, while the investment variable has no influence on Regional Original Income. The most dominant variable influencing Regional Original Income is the variable number of tourist visits.